Basics of Bioinformatics in Biological Research - Kamble, Ashwini; Khairkar, Rajesh (International Journal of Applied Sciences and Biotechnology, 2017)
The concept of laboratory rat is giving way to the computer mouse arose after the famous handshake between Clinton-Blair for the completion of the human genome in April 2003. Bioinformatics is defined as the application of computational techniques to understand and organize the information associated with biological macromolecules. There is availability of large databases of genomic information which has enabled research efforts for discovering methods for diagnosis and treatment of human diseases using DNA microarrays and proteomics experiments. But there are various problems while doing this like it’s always challenging to develop proper and sophisticated analysis method which can properly use genomic data bases considering its and heterogeneity of the data. The main purpose of this first paper is to explore and explain Bioinformatics in a more scientific way, and try highlighting applications of bioinformatics in the medical sector. Int J Appl Sci Biotechnol, Vol 4(4): 425-429